Brooks Range Treeline White Spruce Tree-ring Data (2022) - Colin Maher; Daniel Crawford; Patrick Sullivan (Arctic Data Center, 2023)
Tree-ring widths from 1576 white spruce trees growing at 78 treelines distributed across 19 research sites along a longitudinal gradient in the Brooks Range of northern Alaska. The general purpose of the sampling was to examine west-east variation in white spruce growth responses to changes in climate. Trees were sampled at both high ("alpine") and low elevation treelines ("arctic"). Increment cores were collected in August and September of 2022 as low as possible on each tree (~25 centimeter height). Trees indicated with an "f" were treated with NPK (nitrogen, phosphorus, potassium) fertilizer in June of 2019 and June of 2021.